2017
DOI: 10.1021/acs.jafc.6b05135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Allergenicity at Gly m 4 and Gly m Bd 30K of Soybean after Genetic Modification

Abstract: Despite rapid growth of genetically modified (GM) crops, effective evaluations of genetic modification on allergenicity are still lacking. Gly m Bd 30K is cross-reactive with cow's milk protein casein, Gly m 4, and with birch pollen allergen Bet v 1. Here we compared the allergenicity between GM and non-GM soybeans with respect to the foci Gly m 4 and Gly m Bd 30K. Recombinant allergens of Gly m Bd 30K and Gly m 4 were generated and polyclonal antibodies raised to identify these two allergenic components in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The expression of the P34 allergen protein has also been monitored in the widely grown genetically modified soybeans: No difference between conventional (non-GM) and genetically modified (glyphosate tolerant) soybean was found in gene expression of the P34 allergen in a recent study which also confirmed the immunodominant character of the P34 allergen (TSAI et al, 2017).…”
Section: Gly M Bd 30 K (P34)mentioning
confidence: 84%
“…The expression of the P34 allergen protein has also been monitored in the widely grown genetically modified soybeans: No difference between conventional (non-GM) and genetically modified (glyphosate tolerant) soybean was found in gene expression of the P34 allergen in a recent study which also confirmed the immunodominant character of the P34 allergen (TSAI et al, 2017).…”
Section: Gly M Bd 30 K (P34)mentioning
confidence: 84%
“…Non-GM soybeans (imported from DG Global Inc., Toronto, ON, Canada) and two GM soybeans (GM-1 and GM-2 samples, imported from the United States) were purchased from retailers in Taiwan. The soybeans were fully matured at the R8 stage before harvest and then export to Taiwan [ 17 ]. Soybean samples were steamed for 20 min at 121 °C by autoclave and then dried for 24–72 h in a dryer.…”
Section: Methodsmentioning
confidence: 99%
“…The allergenicity is compared between transgenic and conventional soybeans with respect to the foci Gly m 4 and Gly m Bd 30K in human serum. Patients allergic to soy and those with a history of hypersensitivity to birch pollen and bovine casein might not experience further increased allergic reactions after exposure to GM soybeans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, Gly m Bd 30K/P34, Gly m Bd 28K/P28, and Gly m 5 are classified as major soybean allergens. In contrast, Lu et al and Holzhauser et al only recognized Gly m 5 and Gly m 6 as clinically relevant soybean allergens and classified Gly m Bd 30K/P34, Gly m Bd 28K/P28, lectin, and the lipoxygenase as putative allergens only.…”
Section: Allergenic Soybean Proteinsmentioning
confidence: 99%